PENGARUH INFLASI, TINGKAT SUKU BUNGA, KURS, HARGA MINYAK DUNIA DAN HARGA EMAS DUNIA TERHADAP IHSG DAN JII DI BURSA EFEK INDONESIA - Sartika, Umi (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT The research aims to investigate empirically the influence of selected macroekonomic variables. The research design is associative. Independent variabel are inflation, Bank Indonesia certificate rate, the exchange rate of IDR, World Oil Price and World Gold Price on Indonesia Composite Index and Jakarta Islamic Index at The Indonesia Stock Exchange (IDX). This paper examines the direct effect of selected macroeconomic variabel on Indonesia Composite Index and Jakarta Islamic Index. The data is taken from the monthly closing price of each dependent and independent variables. The sampling method used in this study is the sample saturated and obtained a sample of 60 months of data closing price. The data used are secondary data collection methods of data documentation. The analysis which used in this research is multiple linier regression analysis, F test and t test. The result of calculations using Eviews 8, showed that: the result hypothesis F test, obtained value of Fcompute > Ftable, means that there is the influence of inflation, Bank Indonesia certificate rate, the exchange rate of IDR, World Oil Price and World Gold Price together on Indonesia Composite Index and Jakarta Islamic Index. While result of the hypothesis t test, showed that inflation, Bank Indonesia certificate rate, the exchange rate of IDR, World Oil Price and World Gold Price partially had not influence on Indonesia Composite Index and Jakarta Islamic Index